Geoecologia das paisagens aplicada ao planejamento ambiental na bacia hidrográfica do Rio Pitimbu/RN - Brasil - Lima, Gabriella Cristina Araújo de (2021)
The watershed basin of the Pitimbu River is in the state of Rio Grande do Norte, has an area of 132.46 km², being responsible for the water supply of 35% of the Metropolitan Region of Natal (RMN). It presents a variety of landscape units and economic activities that are linked to the multiple uses of water, which causes an overload on natural resources. Given the context, this research aims to develop environmental planning guidelines for the hydrographic basin of the Pitimbu River, based on an analysis and diagnosis supported by the Geoecology of Landscapes, considering the potentialities and limitations of the inherent landscape features (characteristics) the basin. In methodological terms, the research followed phases applying geoecological analysis, which are: organization and inventory, analysis, diagnosis, and proposition. For this purpose, maps on the scale of 1: 80,000 were prepared, aided by more detailed surveys on a local scale, also subsidizing the elaboration of the land use and coverage map. From the integrated analyzes between physical environmental and socioeconomic factors, it was possible to delimit the four geoecological units of the hydrographic basin, namely: Tabuleiro das Vitórias; Trays of Palmares; Jiqui Trays and Potiguares Deposits. The geoecological units were essential for the discussion about the strengths and weaknesses, as well as subsidizing integrated management strategies for the reality of the basin, where the aspects already mentioned were considered, making a correlation with the use and occupation of the perimeter soil. hydrographic basin. In this way, the integrated management strategies presented here, have as their main objective to be put into practice based on the union between public power, society, and river basin managers. It is expected that from the actions and highlighted data, natural resources, especially water, can be used in a way that is more compatible with the potential and responsiveness of the area. Thus, it is expected that the general results presented here can serve as a basis for maintaining this source.